Sensitivity Test of Bandotan Leaf Extract (Ageratum conyzoides) Against Pseudomonas aeruginosa Bacteria - Masda Admi; Yuni Sari; Rasmaidar Rasmaidar; Amiruddin Amiruddin; T Zahrial Helmi; Yusrizal Akmal; M Isa (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
The leaves of Bandotan (Ageratum conyzoides) are a plant thought to have antibacterial properties. This study aims to determine the sensitivity of Bandotan leaf extract in inhibiting the growth of the bacteria Pseudomonas aeruginosa. This study used a stock extract of Bandotan leaves from the Pharmacology Laboratory and a bacterial isolate of P. aeruginosa in the Microbiology Laboratory of the Faculty of Veterinary Medicine, Universitas Syiah Kuala, which was identified by Gram staining, indole test, Methyl Red test, and confectionery test. The research method was carried out by planting the re-identified bacterial isolates on Nutrient Broth (NB) media, incubated at 37ºC for 24 hours. Then the turbidity composition of the isolates was arranged to match the turbidity in 0.5 McFarland solution. Furthermore, the sensitivity test of the extract on Mueller Hinton Agar (MHA) media was carried out by levelling the bacterial isolates on the surface of the media and attaching a disc containing bandotan leaf extract with a concentration of 25%, 50%, 75% and gentamicin disk as a positive control and distilled water as a negative control. All treatments were incubated at 37ºC for 24 hours, and then the inhibition zone was measured using millimeters (mm) callipers. The results showed that concentrations of 25%, 50% and 75%, respectively, had an inhibition zone of 8.16 mm, 9.82 mm, and 16.08 mm, respectively. In contrast, the average inhibition zone for gentamicin was 25, 30 mm and 0 mm distilled water. Therefore, it can be concluded that the Bandotan leaf extract is sensitive to growth inhibition of P. aeruginosa bacteria.